ANALISIS ORIENTASI POLA BEKERJA CERDAS BERDASARKAN FAKTOR-FAKTOR YANG MEMPENGARUHI KEAHLIAN TENAGA PENJUALAN DALAM AKTIVITAS PENJUALAN DAN DAMPAKNYA TERHADAP KINERJA TENAGA PENJUALAN - Jatmiko, Robby (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2016)
This study analyzes the orientation analysis of intelligent working patternsbased on factors affecting salesperson expertise in sales activities and their impact on salesforce performance. Sampling technique is purposive (purposive sampling) method.Respondents from this study amounted to 105 respondents, where respondents were thesalespeople at Pharmaceutical Large Traders in Semarang. The data analysis tool usedis Structural Equation Modeling (SEM) in AMOS 4.01 program.The results of this research data analysis show the model and research resultscan be received well. And then the results of this study proves that the influence oflearning orientation on salesperson expertise in sales activities is a significant positip.The more effective the implementation of supervisor control orientation on salespeople, thebetter the salesperson's skill in sales activity. The influence of supervisory controlorientation on salesperson expertise in sales activity is a significant positively. And thehigher the skills of a salesperson in sales activity, the better the application of intelligentpatterns of work done by the sales force. And the skills of salespeople in sales activitieshave a significant positive effect on the orientation of intelligent working patterns.